Structural analysis of physical activity, self-efficacy on academic achievement, and critical thinking abilities of elementary school children - Dhedhy Yuliawan; Wawan Sundawan Suherman; Soni Nopembri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
(CT), along with the moderating role of Self-Efficacy (SE) in this relationship. Methods: Data collection was carried out through statistical analysis of test and survey results given to research participants. Results: The results of the analysis indicate that physical activity has a significant influence on AG and CT at the 95% confidence level, which is strengthened by the P value and t statistic which exceed the significance threshold. In addition, Self-Efficacy was also proven to have a significant role in linking physical activity with AG and CT. The implications of this research show the urgency of promoting physical activity as an element of improving academic performance and critical thinking abilities, with a special focus on strengthening self-efficacy. Conclusion: The conclusions of this research can be a guide for policymakers, educators and other stakeholders in designing comprehensive and sustainable education strategies.